The Prevalence of Soil-Transmitted Helminths and Associated Risk Factors among School Children at Sekela Primary School, Western Ethiopia - Addisu Tolera; Mebrate Dufera (Journal of Parasitology Research, 2020)
Soil-transmitted helminth (STH) infections are a major public health problem in tropical and developing countries in relation to poverty, inadequate hygiene, and sanitation. This study was aimed at assessing the status of STH and associated risk factors among school children in the case of Sekela primary school. Cross-sectional descriptive studies were conducted in May 2019 and from 384 children, both males and females of equal proportion were used. A stool sample was collected randomly and examined in the laboratory under a microscope. The quantitative data were analyzed using SPSS version 20. The difference was considered statistically significant at p value = 0.05. The overall STH infections observed in the study area were about 25.78% and were moderate transmission. The predominant helminth was A. lumbricoides (9.86%) followed by hookworm 6.25%, T. trichiura 5%, H. nana 3.10%, and H. diminuta 1.56%. Infections were generally more in males than females, in which 15.36% males and 10.41% females. In the case of age group, age groups between 7-8 years were more infected (13.28%). Infection rate decreases with increasing ages. Multivariate logistic regression analysis result indicated that wearing shoes, hand washing practice, family member, and residence were found to be associated risk factors for STH infections. Being urban dwellers and having family members with less than 2 children were found to be preventive. Lack of latrine, playing barefoot, untrimmed fingernail, eating raw vegetables, and absence of hand washing were major risk factors. In conclusion, the study showed that there was moderate transmission of infection among the study participants. Community-based health education using media, morbidity control through deworming, and improving sanitation should be strengthened as a measurement to control the transmission rate.